2001
DOI: 10.1021/bi010333o
|View full text |Cite
|
Sign up to set email alerts
|

Enthalpic and Entropic Contributions to the Mutational Changes in the Reduction Potential of Azurin

Abstract: The changes in the reduction potential of Pseudomonas aeruginosa and Alcaligenes denitrificans azurins following point mutations and residue ionizations were factorized into the enthalpic and entropic contributions through variable temperature direct electrochemistry experiments. The effects on the reduction enthalpy due to changes in the first coordination sphere of the copper ion, as in the Met121Gln and Met121His variants of A. denitrificans azurin, insertion of a net charge and alteration in the solvation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
63
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(75 citation statements)
references
References 42 publications
11
63
1
Order By: Relevance
“…These observations are consistent with the predictions based on Coulomb's law as discussed above. Moreover, the sign of DH°(i.e., negative DH°) appears to be consistent with electrostatic considerations in other proteins [10,11,12].…”
Section: Enthalpic Changes and Electrostatic Interactionssupporting
confidence: 83%
See 2 more Smart Citations
“…These observations are consistent with the predictions based on Coulomb's law as discussed above. Moreover, the sign of DH°(i.e., negative DH°) appears to be consistent with electrostatic considerations in other proteins [10,11,12].…”
Section: Enthalpic Changes and Electrostatic Interactionssupporting
confidence: 83%
“…Most notably for these two charged mutations, the entropic contribution to the reduction potential is larger and opposite in sign relative to the enthalpic contribution. This phenomenon has been observed for other electron transfer proteins ( [12] and references therein).…”
Section: Entropic Changes and Monopolessupporting
confidence: 72%
See 1 more Smart Citation
“…Multiple studies have suggested that the remaining influences on the potential of the Cu site are from hydrophobic and hydrogen bonding interactions in the secondary coordination sphere [9,32,[35][36][37][38][39][40], however these hypotheses require empirical verification [1]. Compiled works have suggested that the secondary coordination sphere can tune the reduction potential through factors such as varied water solvation, protein rigidity, electrostatics and dipole moments, and exogenous free ions which leads to a complex interplay of the entropic and enthalpic terms of each redox state [4,9,28,35,36,[41][42][43][44][45][46][47][48][49].…”
Section: Introductionmentioning
confidence: 99%
“…Site-directed point mutation of the axial ligand has been carried out for blue copper proteins. It has been reported that the replacement of Met at the axial ligand by Gln causes the negative shift in the formal potential of the type I Cu site in blue copper proteins [7][8][9][10][11]. In contrast, the replacement of Gln by Met causes the positive shift in the formal potential [12,13].…”
Section: Introductionmentioning
confidence: 99%